(untitled) (Atlas Journal of Biology, 2019)
English: Effects of structure and soil amendments on percentages of amino acids were examined with three hypotheses for the rare, ancient, drought resistant, indigenous Andean crop plant, Mirabilis expansa (Ruiz and Pav.) Standl. (Nyctaginaceae), grown in southern Illinois. ANOVA and LS-Means analyses were run as pair-wise comparisons. Percentages of amino acids, crude protein, and total protein were dependent variables. Peat and steer manure percentages, used to amend sand plots at the time of their construction, were the soil amendments. Significance for p-values was at .05 or less. ANOVAs indicated several amino acids were present in significantly different amounts between roots and leafy parts of plants. There was a statistically inconsistent effect from peat, and slight significance from steer manure. Exploratory analyses also indicate significantly different amounts of some amino acids between two indigenous varieties of the crop. Spanish: Efectos de la estructura y el suelo enmiendas sobre porcentajes de aminoácidos fueron examinados con tres hipótesis para rara, antiguos, resistentes a la sequía, indígenas andinos cultivo planta Mirabilis expansa (Ruiz and Pav.) Standl. (Nyctaginaceae), crecido en el sur de Illinois. ANOVA y análisis de LS medios fueron funcionados en SAS como comparaciones de pares. Porcentajes de proteína cruda, aminoácidos y proteínas totales fueron las variables dependientes. Porcentajes de estiércol turba y buey, utilizados para modificar parcelas de arena en el momento de su construcción, fueron enmiendas de suelo. Es de importancia para los valores de p.05 o menos. ANOVA han indicado que varios aminoácidos estaban presentes en cantidades significativamente diferentes entre las raíces y las partes de las plantas. Hubo un efecto estadísticamente inconsistente de la turba y leve importancia del estiércol de buey. Análisis exploratorios también indican significativamente diferentes cantidades de algunos aminoácidos entre dos variedades autóctonas de la cosecha.